Утилізація відходів як перспективна галузь національної економіки - Назаренко, Олена Василівна; Решетняк, Наталя Борисівна (НТУ "ХПІ", 2016)
Розглядаються світові досягнення у поводженні з відходами, які полягають у роздільному збиранні, сортуванні, термічній переробці сучасними методами, а також можливості вторинного використання металів, пластмас, паперу, скла тощо. Запропоновано створення в Україні цілісної галузі утилізації відходів, яка може бути прибутковою і одночасно сприятиме очищенню навколишнього середовища. Зроблено висновки про необхідність залучення до роботи в галузі підприємств малого та середнього бізнесу, закордонних інвестицій.

Discusses the ways of solving the problem of waste disposal both in Ukraine and in leading foreign countries. Analyzed best world achievements in waste management, which is to separate the collection of additional sorting, thermal processing by modern methods, and the possibility of secondary use of metals, plastics, paper, glass and the like. Noted the importance of more fuel gas and heat energy during thermal trea tment or incineration to meet the needs of the population. Proposed General approaches and a number of proposals for the establishment in Ukraine of a holistic waste management that can operate profitably and at the same time promote environmental depollution. The conclusions about the necessity of adopting international experience, involvement in industry of the enterprises of small and medium business, foreign investment. Work in this area should be controlled by the public.
Waste management as a promising sector of the national economy
Keywords: навколишнє середовище; утилізація відходів; методи; сортування; захоронення; компостування; термообробка; розвиток сталий; забезпечення; environment; waste disposal; methods; sorting; dumping; composting; heat treatment; sustainable development